Scientific American. – 1870. – Vol. 23, № 24 - б/а (New York. Munn & Company, 1870)
A weekly journal of practical information, art, science, mechanics, chemistry and manufactures.
З фонду Центральної наукової бібліотеки Харківського національного університету імені В.Н. Каразіна.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Mass communication; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; December 10, 1870